2005
DOI: 10.1111/j.1600-0501.2005.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

New formation of periodontal tissues around titanium implants in a novel dentin chamber model

Abstract: Direct bone-to-implant contact, defined as "osseointegration", is considered most optimal for long-term stability and survival of dental implants. However, the possibility of the formation of a tooth-like attachment apparatus around implants has also been demonstrated. The purpose of this study was to explore the formation of periodontal tissues around titanium implants using a novel and unique experimental model. After resection of the crowns of the maxillary canine teeth in nine mongrel dogs, the roots were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 22 publications
(50 reference statements)
1
34
0
5
Order By: Relevance
“…In other words, it should be attempted to achieve an implant position where all boundaries are formed by bone, since, according to current and established principles of osseointegration [31], only direct bone-implant contact without fibrous tissue or other dental materials is accepted as a successful implant interface. If this is the case, complete osseointegration of the implant will be achieved and the formation of a fibrous tissue sheath around the implant [18,19], can be avoided. Here again it has to be mentioned as a limitation that such data could not be collected as part of this case series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, it should be attempted to achieve an implant position where all boundaries are formed by bone, since, according to current and established principles of osseointegration [31], only direct bone-implant contact without fibrous tissue or other dental materials is accepted as a successful implant interface. If this is the case, complete osseointegration of the implant will be achieved and the formation of a fibrous tissue sheath around the implant [18,19], can be avoided. Here again it has to be mentioned as a limitation that such data could not be collected as part of this case series.…”
Section: Discussionmentioning
confidence: 99%
“…Hürzeler et al [18] also demonstrated that the intentional preservation of the coronal buccal root portion can help to ensure the physiological preservation of labial and buccal bone structures if the implant is placed in contact to this natural tooth fragment (shield). However, this approach is associated with certain risks, such as the formation of a peri-implant periodontal membrane [19] or the development of peri-implant infections, as well as resorption associated with the usual biological long-term complications that may occur. These occur especially in the presence of pre-exiting or developing periodontal or endodontic infections or inflammations of the retained tooth fragments.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of cementoblasts covering the cementum of adjacent roots, after having migrated to form the cementum-like layer, also should be considered. 25 The cementum-like layer contained some collagen fibrils into its milieu; this is somewhat similar to the acellular extrinsic fiber cementum that is formed by fibroblasts during cementogenesis. 20 Nevertheless, although the layer had a cementum-like appearance, it did not contain inserted collagen bundles (Sharpey's fibers), leaving it toward the adjacent periodontal ligament.…”
Section: Discussionmentioning
confidence: 86%
“…The discovery of a periodontal ligament around titanium implants opens new perspectives in implantology. Parlar et al (Parlar et al, 2005) performed unique experiment on mongrel dogs to explore the formation of periodontal tissues around titanium implants using maxillary canine roots. They created chambers within the roots and prepared slits in the cavity walls to connect the chamber to the periodontal space.…”
Section: Future Researchmentioning
confidence: 99%